ТЕХНОЛОГІЯ КОМУНІКАТИВНО-СИТУАТИВНОГО МОДЕЛЮВАННЯ У ПРОФЕСІЙНО СПРЯМОВАНОМУ НАВЧАННІ ІНОЗЕМНИХ МОВ У ПЕДАГОГІЧНОМУ УНІВЕРСИТЕТІ (Педагогіка вищої та середньої школи, 2022)
The actual problems of professionally oriented foreign language teaching o f the pedagogical university students are considered in the article. The author substantiates the using of the modelling technology of communicative situations to increase the efficiency of foreign language training for professional purposes.